Reduksi Limbah Plastik Menjadi Batako Press Melalui Pemberdayaan Kelompok Karang Taruna Terpadu Desa Cenrana, Bone - Lukman; Romi Adiansyah; Andi Muhammad Irfan Tauvan Asfar; Andi Muhamad Iqbal Akbar Asfar; Andi Nurannisa; Nurhaerani Ramli; M. Nasrul Asis (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The quantity of plastic waste remains a crucial problem for the community in Cenrana Village. Because of the lack of public awareness of the dangers of plastic waste, handling is carried out only in the form of burning. However, its handling is still considered ineffective. Therefore, this PKM program was implemented to provide a solution for the reduction of plastic waste through the manufacture of press bricks, an environmentally friendly building construction material. The implementation method is carried out through three main stages, namely, counseling, training, assistance, through these three main stages, partners can innovate themselves and even improvise themselves regarding the use of plastic waste into press bricks as a form of handling the quantity problem that partners have been facing. Through the creative recycling of plastic waste, we can expand the scope of applicationstion and create new opportunities in the circular economy. The increase in partner knowledge through the Observational Sheet shows results of 90%, and production and supporting skills with an increase of 90% and 80%, respectively. The increase in skills obtained by partners through this PKM program provides a solution to the reduction of plastic waste that has been faced by the people of Cenrana Village and provides added value to plastic waste as economically valuable products, thus supporting the plastic-free movement in 2025.